Romanistiken i Sverige: Tradition och förnyelse (romanica gothoburgensia, 2019)
The Romance languages are the Indo-European languages developed from Latin. The term "Romance Languages" also refers to the academic discipline, which studies the Romance languages and literature from the areas where the Romance languages are spoken. This discipline has a long tradition in Sweden. Swedish academic education and research in the Romance languages forms the subject of this anthology, whose contributions are written by 22 different researchers active in the field. The anthology examines the historical development of the study of the Romance languages in Sweden, as well as important trends in current education and research. The question of what characterizes the Romance languages as an academic discipline in Sweden today is thoroughly discussed in several of the contributions. The book brings a metadisciplinary perspective in the sense that it is the discipline itself, Romance languages – or some aspect of it – that constitutes the object of study. It is aimed at anyone with an interest in university and scholarly history and the development and position of academic language subjects in a Swedish university context. In addition, several of the contributions are of relevance for readers with an interest in language didactics and for pedagogical research on language teaching in higher education. The hope is that the reflections and investigations gathered in this anthology will serve as a starting point for the future development of the study of the Romance languages in Sweden.